2007
DOI: 10.1029/2005jg000125
|View full text |Cite
|
Sign up to set email alerts
|

Mapping wildfire danger at regional scale with an index model integrating coarse spatial resolution remote sensing data

Abstract: [1] Wildfires are a prevalent natural hazard in the south of France. Planners need a permanent fire danger assessment valid for several years over a territory as large and heterogeneous as Midi-Pyrénées region. To this end, we developed an expert knowledgebased index model adapted to the specific features of the study area. The fire danger depends on two complementary elements: spatial occurrence and fire intensity. Among the GIS layers identified as input variables for modeling, vegetation fire susceptibility… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0
1

Year Published

2007
2007
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(27 citation statements)
references
References 28 publications
(35 reference statements)
0
26
0
1
Order By: Relevance
“…All the study area was submitted to summer drought to various extents. The annual Relative Greenness Index (annual RGRE) was previously used to map vegetation status for fire danger assessment in a non-Mediterranean context (Chéret and Denux, 2007). For this study, we proposed an annual RGRE index adjusted to the vegetative growing season observed for this Mediterranean site.…”
Section: Indicators and Fire Danger Mapsmentioning
confidence: 99%
See 2 more Smart Citations
“…All the study area was submitted to summer drought to various extents. The annual Relative Greenness Index (annual RGRE) was previously used to map vegetation status for fire danger assessment in a non-Mediterranean context (Chéret and Denux, 2007). For this study, we proposed an annual RGRE index adjusted to the vegetative growing season observed for this Mediterranean site.…”
Section: Indicators and Fire Danger Mapsmentioning
confidence: 99%
“…As input data for static risk models, high-spatial-resolution images can be processed to map fuel and ignition parameters directly or by identifying vegetation types (Chuvieco et al, 2003b). Complementarily, coarse-spatial-resolution data can be useful in assessment of the fuel model (Burgan et al, 1998;Chéret and Denux, 2007). Dynamic approaches of fire risk can integrate frequent acquisition of images, usually at coarse spatial resolution, to map daily updates of vegetation status.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this special section, several papers explore the use of satellite remote sensing data for mapping of vegetation cover for use in wildfire danger assessment. Cheret and Denux [2007] developed an approach for assessing wildfire danger using maps of vegetation cover derived from an analysis of coarse resolution SPOT‐Vegetation data. These data were combined with information on topography, fire ignitions, and climatic indices, derived from analysis of time series SPOT‐Vegetation data (see section 2.2.2 below).…”
Section: Summary and Context Of The Papers Of The Special Sectionmentioning
confidence: 99%
“…Even at such a time when technological advancement in data processing, storage and communication enables ever higher spatial resolutions from airborne and satellite sensors, the use of coarser resolution data still has a very firm place in the remote sensing field where broad-scale monitoring is required, such as the monitoring of algal blooms (Ahn and Shanmugam, 2006), assessing risks of fire (Chéret and Denux, 2007;A. and R., 2008) or drought (Rojas et al, 2011), the development of land surface models (Jarlan et al, 2005), the assessment of animal stocking rates (Hunt and Miyake, 2006) and the mapping of shorelines (M. -Muslim et al, 2007).…”
Section: Other Applications Of Gm Datamentioning
confidence: 99%